2010
DOI: 10.1590/s0100-29452010005000023
|View full text |Cite
|
Sign up to set email alerts
|

Influência da altitude na qualidade das uvas 'Chardonnay' e 'Pinot Noir' em Minas Gerais

Abstract: RESUMO -No Sul e Sudeste brasileiros, o excesso de chuvas durante o período de maturação afeta negativamente a qualidade dos vinhos tintos. Por outro lado, estas regiões possuem potencial para a elaboração de espumantes, uma vez que, para a elaboração desta bebida, a uva é colhida antes de completar o amadurecimento. No Estado de Minas Gerais, as condições de verão chuvoso estão presentes em todas as regiões de potencial vitícola, e a variação de altitude entre elas pode exercer infl uência na composição das u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
2
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 10 publications
2
13
2
6
Order By: Relevance
“…Figure 1 shows that the weight of pineapple guava fruits at harvest is higher in fruits produced at higher altitudes (Tenjo) where the cumulative radiation is greater, and a greater number of calendar days and less thermal time (GDD) is required from anthesis to harvest (Table 1). These results are consistent with those observed by Regina et al (2010) (2008) found similar results for pineapple guava fruits of clone 41 and indicated that the fruits with the lowest fresh weight values were located in the inner core of the canopy, which has a low incidence of light radiation, thus supporting light radiation as "the luminosity factor essential for proper photosynthesis and the production of photoassimilates for fruit development. "…”
Section: Fruit Growthsupporting
confidence: 91%
See 1 more Smart Citation
“…Figure 1 shows that the weight of pineapple guava fruits at harvest is higher in fruits produced at higher altitudes (Tenjo) where the cumulative radiation is greater, and a greater number of calendar days and less thermal time (GDD) is required from anthesis to harvest (Table 1). These results are consistent with those observed by Regina et al (2010) (2008) found similar results for pineapple guava fruits of clone 41 and indicated that the fruits with the lowest fresh weight values were located in the inner core of the canopy, which has a low incidence of light radiation, thus supporting light radiation as "the luminosity factor essential for proper photosynthesis and the production of photoassimilates for fruit development. "…”
Section: Fruit Growthsupporting
confidence: 91%
“…An analysis of variance (ANOVA) showed statistical differences between locations and harvests (Table 2) for weight, diameter and length, indicating that the values of these parameters at harvest are heavily influenced by the weather conditions recorded at each location and each harvest during fruit growth (Fischer et al, 2007;Martínez-Vega et al, 2008;Regina et al, 2010).…”
Section: Physicochemical Characteristics At Harvestmentioning
confidence: 99%
“…However, a good alternative to wine producers is the white grapes cultivars, because the quality of their wines, in addition to not depending on phenolic maturation, accepts higher levels of total acidity. Little to no information is available in literature regarding the behavior of new white grape varieties in different Brazilian regions [7].…”
Section: Introductionmentioning
confidence: 99%
“…Entre as cultivares de Vitis labrusca, a 'Bordô' é bastante plantada no Brasil (32.000 t) para produção de vinho tinto, suco, vinagre, geleias e, por sua precocidade, é consumida in natura (RIZZON et al, 2000).…”
Section: Introductionunclassified
“…Via de regra, nas regiões Sul e Sudeste brasileiras, o período de maturação da cultivar Bordô coincide com o período chuvoso (REGINA et al, 2010), e há relatos dos produtores locais que, por esta razão, a uva 'Bordô' não atinge na colheita uma relação SST/ATT alta o suficiente para produzir bons vinhos. Isto aparentemente desqualifica o plantio de uva 'Bordô' nesta região para a atividade vinícola.…”
Section: Introductionunclassified